Isoquercetin Improves Inflammatory Response in Rats Following Ischemic Stroke - Shi, Yunwei; Chen, Xinyi; Liu, Jiaxing; Fan, Xingjuan; Jin, Ying; Gu, Jingxiao; Liang, Jiale; Liang, Xinmiao; Wang, Caiping (Frontiers in Neuroscience, 2021)
Inflammatory response contributes to brain injury after ischemia and reperfusion (I/R). Our previous literature has shown isoquercetin plays an important role in protecting against cerebral I/R injury. The present study was conducted to further investigate the effect of isoquercetin on inflammation-induced neuronal injury in I/R rats with the involvement of cAMP/PKA and I-κB/NF-κB signaling pathway mediated by TLR4 and C5aR1. In vivo middle cerebral artery occlusion and reperfusion (MCAO/R) rat model and in vitro oxygen-glucose deprivation and reperfusion (OGD/R) neuron model were used. MCAO/R induced neurological deficits, cell apoptosis and release of cytokines such as TNF-α, IL-1β and IL-6 in ischemia brain in rats.Simultaneously, expression of TLR4 and C5aR1 were significantly up-regulated in both MCAO/R rats and OGD/R neurons, accompanied with the inhibition of cAMP/PKA signaling and activation of I-κB/NF-κB signaling in cortex of MCAO/R rats. Over-expression of C5aR1 in neurons induced decrease of cell viability, exerting similar effects with OGD/R injury. Isoquercetin acted as a neuroprotective agent against I/R brain injury to suppress inflammatory response and improve cell recovery by inhibiting TLR4 and C5aR1 expression, promoting cAMP/PKA activation, and inhibiting I-κB/NF-κB activation and Caspase 3 expression. TLR4 and C5aR1 contributed to inflammation and apoptosis via activating cAMP/PKA/I-κB/NF-κB signaling during cerebral I/R, suggesting that this signaling pathway may be a potent therapeutic target in ischemic stroke.Isoquercetin was identified as a neuroprotective agent, which maybe a promising therapeutic agent used for the treatment of ischemic stroke and related diseases.